New Lives in Anand : Building a Muslim Hub in Western India - Verstappen, Sanderien (Book collections on Project MUSE., 2021)
"In 2002 widespread communal violence tore apart hundreds of towns and villages in rural parts of Gujarat, India. In the aftermath, many Muslims living in Hindu-majority villages sought safety in the small town of Anand, some relocating with the financial assistance of their relatives overseas. Following such dramatic displacement and disorientation, Anand emerged as a site of opportunity and hope. For its residents and transnational visitors, Anand's Muslim area is not just a site of marginalization; it has become an important focal point and regional center from which they can participate in the wider community of Gujarat and reimagine society in more inclusive terms. This compelling ethnography shows how in Anand the experience of residential segregation led not to estrangement or closure but to distinctive practices of mobility and exchange that embed Muslim residents in a variety of social networks. In doing so, New Lives in Anand moves beyond established notions of ghettoization to foreground the places, practices, and narratives that are significant to the people of Anand. It asks how people get on with their lives after an episode of violence to create new spaces and societies and to reconfigure their sense of belonging"--